The Analysis of Management and Timber Trade System of Gelam (Melaleuca cajuputi) From Peat Swamp Forest in South Kalimantan - Yudi Firmanul Arifin; Siti Hamidah; Yulian Firmana Arifin (Center for Journal Management and Publication, 2014)
Until now the raw material of wood especially Gelam (Melaleuca cajuputi) available for supporting the construction of housing and other infrastructures is increasingly large in Indonesia. On the Island of Borneo that partly consists of swamps needs Gelam very large and continuous, particularly for residential development. However, areas of peat swamp forest habitat of this plant from year to year are degradation and shrinkage. This situation is a very big influence on the population of Gelam, while the management and timber trade systems are not well regulated. This study aims to analyze the management and timber trade systems of Gelam particularly in South Kalimantan to provide input to the policy holder in the preservation of Gelam. The method was used a field survey and interviews with traders and policy holders related regulations. The results showed in South Kalimantan the potency of Gelam is only 2,9-7,1 m3/ha and decreasing yearly. Normally Gelam with a diameter <4 cm have been cut down, as well as > 30 cm. These dimensions should not be cut because of <4 cm too young and > 30 cm can be used as seed sources. Gelam derived from peat swamp forest, which mostly comes from the Batola District and some came from Kapuas District of Central Kalimantan. Distributions of Gelam were starting gatherers logging in the forest then sold to small gatherers, next to the large gatherers and distributed to all districts/cities in South Kalimantan, wood processing industries, and some of them were sent to Java. The silviculture system of Gelam was using selective cutting. Classification of wood sizes traded by the diameter divided into 3-4cm, 5-6cm, 7-8cm, 9-10cm, 11-12cm, 13-14cm, 15-19cm and > 20cm to 4m long. Its use consists of a small diameter (3-10cm) for foundry building and firewood, while the large diameter (10-20cm) for the construction of houses in swampy areas, and waste as well as the stems are bent and deformed used for firewood. Until now Gelam becomes into the business community and potential sources of local government revenue if managed properly. However, due to the rules of management and administration in South Kalimantan was not going well, thus threatening the sustainability especially with the growing extent of peat lands being converted into palm oil plantations.